Influence of Organizational Factors on In-House Software Quality Assurance in Strategic State Corporations in Kenya (International Journal of Scientific Research and Management (IJSRM), 2017)
Purpose: The purpose of the study was to determine the influence of organizational factors on in-house software quality assurance in Strategic state corporations in Kenya. Methodology: The study used quantitative research method and applied Survey research design. The research population and target group comprised 6large Strategic state corporations, three in Transport and Infrastructure sector and three in the Energy sector. These are playing a critical to the Kenyan economy and the attainment of Vision 2030. These corporations have a combined ICT work force of approximately 300 personnel. From the research population, a sample of 169 respondents was scientifically selected and administered with questionnaires using a drop and pick method. A multiple linear regression model was used to analyze the data using statistical package for the social sciences (SPSS). Results: The study found that 38.5% of the variation in In-house Software Quality Assurance in Strategic state corporations can be explained by Organizational factors. The result of coefficients to the estimates was 0.000 and hence significant at the 0.05 level of significance. This indicated that Organizational factors positively and significantly influence In-house Software Quality Assurance in Strategic state corporations. The results also found that Government regulation had a partial intervening effect on the relationship between Organizational factors and in-house Software Quality Assurance in Strategic state corporations. Unique contribution to theory, practice and policy: The findings of this study are useful to the Government, Strategic state corporations, Policy makers, Scholars, Software developers, IT consultants and other state corporations. There is need to develop policies and software development frameworkthat will be create a conducive Organizational environment that supports in-house development of quality software